2013
DOI: 10.1016/j.celrep.2013.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Protective Roles for Caspase-8 and cFLIP in Adult Homeostasis

Abstract: Summary Caspase-8 or cFLIP deficiency leads to embryonic lethality in mice due to defects in endothelial tissues. Caspase-8−/−, RIPK3−/−, but not cFLIP−/−, RIPK3−/−, double-knockout animals develop normally, indicating that caspase-8 antagonizes the lethal effects of RIPK3 during development. Here we show that the acute deletion of caspase-8 in the gut of adult mice induces enterocyte death, disruption of tissue homeostasis and inflammation, resulting in sepsis and mortality. Likewise, acute deletion of caspas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
149
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(156 citation statements)
references
References 39 publications
5
149
1
1
Order By: Relevance
“…Recent data has clearly shown a vital role for RIPK3 during embryogenesis, but this is only revealed in the absence of caspase-8 or FADD. In adult mice, disabling the ability of caspase-8 to inhibit RIPK3 (by either caspase-8 or FLIP deletion) in specific organs also leads to RIPK3-dependent inflammation and necrosis in the intestine and skin (Bonnet et al, 2011;Panayotova-Dimitrova et al, 2013;Weinlich et al, 2013;Welz et al, 2011). Recent studies also argue that RIPK3 can directly induce inflammation even in the absence of cell death, thereby complicating direct implication of RIPK3-dependent necroptosis in any given process (Kang et al, 2013;Vince et al, 2012).…”
Section: In Vivo Functions Of Necroptosismentioning
confidence: 99%
“…Recent data has clearly shown a vital role for RIPK3 during embryogenesis, but this is only revealed in the absence of caspase-8 or FADD. In adult mice, disabling the ability of caspase-8 to inhibit RIPK3 (by either caspase-8 or FLIP deletion) in specific organs also leads to RIPK3-dependent inflammation and necrosis in the intestine and skin (Bonnet et al, 2011;Panayotova-Dimitrova et al, 2013;Weinlich et al, 2013;Welz et al, 2011). Recent studies also argue that RIPK3 can directly induce inflammation even in the absence of cell death, thereby complicating direct implication of RIPK3-dependent necroptosis in any given process (Kang et al, 2013;Vince et al, 2012).…”
Section: In Vivo Functions Of Necroptosismentioning
confidence: 99%
“…[1][2][3] The function of RIPK3 to promote necroptosis can be induced by the activity of receptor-interacting protein kinase-1 (RIPK1), 4 and is antagonized by the proteolytic activity of a complex formed by RIPK1, FADD, caspase-8 and c-FLIP L . [5][6][7][8][9][10] Inactive RIPK1 functions to inhibit RIPK3 activation, even under conditions in which RIPK3 is activated independently of RIPK1. [11][12][13] These complex interactions help to account for the lethal effects of ablating FADD, caspase-8 or RIPK1.…”
mentioning
confidence: 99%
“…Studies in recent years have demonstrated the involvement of necroptosis in a number of pathophysiological processes, such as atherosclerosis (6), skin inflammation (7)(8)(9), chronic intestinal inflammation (10, 11), Gaucher's disease (12), acute liver injury (13,14), and heightened intestinal inflammation (15).…”
mentioning
confidence: 99%